Factores de riesgo maternos neonatales asociados a la enfermedad de membrana hialina en recién nacidos pretérmino y sus consecuencias en la unidad de neonatología en el hospital Isidro Ayora - Loja durante el periodo febrero - agosto del 2013 - Luna Jara, Tania Elizabeth (2014)
Knowledge of maternal and neonatal factors associated risk Hyaline Membrane Disease is a mainstay in the management prenatal and newborn preterm aims to provide comprehensive care from conception and thus reduce the incidence and mortality. The descriptive, prospective, cross-sectional study was conducted to determine factors maternal and neonatal risks associated with EMH and its implications in the period February - August 2013 The particular sample was 40 cases diagnosed RN EMH, the data were collected through a data collection sheet of maternal and neonatal medical records, record daily changes, and structured interview the mother. Nulliparous women 70% (OR, 4; was obtained as a result that the factors that are associated EMH: teenage pregnancy in 52.5% (95% CI 1.14 to 7.75 RM 2.98). , 3, 95% CI 1.65 to 11.19), inadequate prenatal care 57.5% (OR: 2.81, 95% CI 1.11 to 7.15), pathologies in the Third Quarter (OR: 2.73 95% CI 0.94 to 7.95), fetal disproportion - pelvic: 57.5%, 82.5% elective caesarean section, neonatal factors such as prematurity by 90% (OR: 10.58, 95% 3,13- 35.8), 60% male gender (OR: 4.05, 95% CI 1.54 to 10.6), no administration of corticosteroids 42.5%, mild to moderate birth asphyxia 52.5%. Comorbidities are associated pneumonia: 75%, hyperbilirubinemia multifactorial 22.5%, sepsis 17.5%, 12.5% bronchopulmonary dysplasia, necrotizing enterocolitis 10%, conditions that determined the status and clinical outcome of patients, a 87.5% was favorable with a good prognosis, and determining mortality of 12.5% of cases. Knowledge of this health problem is intended to help improve the timely, comprehensive, effective, efficient, quality care and warmth in the maternal environment - neonatal, and lower rates of neonatal mortality and prematurity as a key factor in the development of SDR I. Keywords: Hyaline Membrane Disease, risk factors; clinical course; morbidity – mortality.